2015
DOI: 10.1007/s40291-015-0157-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel T-Cell Assays for the Discrimination of Active and Latent Tuberculosis Infection: The Diagnostic Value of PPE Family

Abstract: This study confirms IL-2 induced by PE35 and PPE68 as a sensitive and specific biomarker and highlights IL-2 as new promising adjunct markers for discriminating of LTBI and active TB disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…PPE68, EccD1, EspJ and PE35 were less frequently recognized in this study compared to previous reports213039, suggesting that our selected regions did not contain the immunogenic epitopes and warrants further exploration.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…PPE68, EccD1, EspJ and PE35 were less frequently recognized in this study compared to previous reports213039, suggesting that our selected regions did not contain the immunogenic epitopes and warrants further exploration.…”
Section: Discussioncontrasting
confidence: 60%
“…One of these Ags, ESX-1 substrate protein C, (EspC, Rv3615c), has previously been identified as a highly recognized and Mtb specific antigen1319202122. Other potential candidates include the ESX-1 associated EspJ (Rv3878)2324, EspF (Rv3865)2526272829, the RD1 encoded PPE68 (Rv3873)23, PE35 (Rv3872)30, EccD1 (Rv3877)31 and the RD7 encoded Rv234832 (Table 1). By screening fragments in pools of three to seven peptides, we aimed to cover several antigens in the cocktail while retaining a low total number of peptides.…”
mentioning
confidence: 99%
“…The identification of valuable M. tuberculosis antigens is vital to the improvement of serodiagnostic methods of TB. In recent years, comparative genomic studies have identified some promising recombinant proteins for TB serodiagnosis such as ESAT‐6, CFP‐10, Hsp60 (Shekhawat et al ., ), PE35 (Baumann et al ., ), PPE57 (Chen et al ., ), PPE68 (Pourakbari et al ., ), Rv1168c, Rv1985c and Rv3878 (Dosanjh et al ., ). The combination of antigens ESAT‐6 and CFP‐10 has been used to identify individuals with active TB in commercial tests.…”
Section: Discussionmentioning
confidence: 99%
“…One of the highly immunogenic PPE protein, PPE55 (Rv3347c) was reported to be expressed during incipient and clinical TB and suggested to be useful for differentiating between latent TB and incipient, subclinical TB [ 32 ]. Another group studied IL-2 response against PE35 and PPE68 between active TB patients and LTBI and concluded that PPE68 induced IL-2 could be used as a sensitive and specific biomarker for discriminating TB from LTBI [ 33 ]. All these studies made an effort to identify PE/PPE proteins to be used as diagnostic antigen for LTBI, however, major limitations of these studies was the use of low number of samples from the LTBI group.…”
Section: Discussionmentioning
confidence: 99%